A combined approach for segment-specific analysis of market basket data - Yasemin Boztuğ; Thomas Reutterer (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
There are two main research traditions for analyzing market basket data that exist more or less independently from each other, namely exploratory and explanatory model types. Exploratory approaches are restricted to the task of discovering cross-category interrelationships and provide marketing managers eith only very limited recommendations regarding decition making. The latter type of models focus on estimating the effects of category-level marketing mix variables on purchase incidences assuming cross-category dependencies. We propose a procedure that combines these two modeling approaches in a novel two-stage procedure for analyzing cross-category effects based on shopping basket data: In a data compression step we first derive a set of market basket prototypes and generate segments of households with internally more distinctive (complementary) cross-category interdependencies. Utilizing the information on categories that are most responsible for prototype construction, segment-specific multivariate logistic models are estimated in a second step. Based on the data-driven way of basket construction, we can show significant differences in cross-effects and related price elasticities both across segments and compared to the global (segment-unspecific) model.
Keywords: C31; C33; C35; C63; M31; 330; Marketing; Choice Models; Market Basket Analysis; Cross-Category Effects; Segmentation; Konsumentenverhalten; Einzelhandel; Multivariate Analyse; Marktforschung